2023
DOI: 10.1007/s11356-023-26671-5
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the environmental Kuznets curve, pollution haven, and pollution halo hypotheses with carbon efficiency in China: A dynamic ARDL simulations approach

Abstract: Given a new perspective on the environmental hypothesis, this paper systematically investigates the validity of the environmental Kuznets curve (EKC), pollution haven, and pollution halo hypotheses using carbon efficiency as the dependent variable. Applying the dynamic autoregressive distributed lag simulations based on the annual time series data over the period 1990–2019, the study found that real GDP per capita has negative effects on China’s environmental quality both in the short and long run, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Furthermore, the positive correlation between the GDP per capita and sustainable development aligns with the Environmental Kuznets Curve (EKC) hypothesis, which theorizes that environmental quality initially deteriorates during economic development but improves once a certain income level is achieved [44]. A case study focusing on China, conducted by [45], exemplifies this, as it shows how the nation's increasing GDP per capita has coincided with advancements in environmental quality and sustainable practices. Nevertheless, it is worth noting that the GDP per capita does not serve as an impeccable measure of well-being or sustainable development.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, the positive correlation between the GDP per capita and sustainable development aligns with the Environmental Kuznets Curve (EKC) hypothesis, which theorizes that environmental quality initially deteriorates during economic development but improves once a certain income level is achieved [44]. A case study focusing on China, conducted by [45], exemplifies this, as it shows how the nation's increasing GDP per capita has coincided with advancements in environmental quality and sustainable practices. Nevertheless, it is worth noting that the GDP per capita does not serve as an impeccable measure of well-being or sustainable development.…”
Section: Discussionmentioning
confidence: 61%
“…On the contrary, the finding of this study is in disagreement with Balcilar et al ( 2023a ), who found that the TNCs who undertake FDI behave in such a way that leads to environmental damage in African countries. Ozkan et al ( 2023a ) and Pata et al ( 2023a ) also revealed the negative impact of FDI on environmental quality in China. This is because the motive behind their operations is anchored on profit accumulation.…”
Section: Resultsmentioning
confidence: 94%
“…The bibliometric analysis indicates that there is an upward trend in the number of research in the field of green economy, circular economy and sustainable development; however, there are country-specific differences in terminology (Ali et al, 2021). At that, all researchers tend to believe that the efficient use of resource, the circular economy, innovation, social integration, ecosystem protection, etc., contribute to the coordinated development of the economy, society and the environment and the achievement of sustainable development (Ozkan et al, 2023). Sustainability and the green economy in Russia are also deeply investigated (Bobylev and Solovyeva, 2017;Zhironkin et al, 2017;Popkova et al, 2018;Karieva et al, 2020;Tulupov et al, 2020;Lavrikova et al, 2021;Kuznetsova et al, 2022;Tagaeva et al, 2022).…”
Section: Digital Economy and Sustainable Developmentmentioning
confidence: 99%